PERKEMBANGAN ILMU PENGETAHUAN, SISTEM PEMERINTAH DAN ILMU TASAWUF PADA DINASTI ABBASIYAH - Mohammad Anggi Hidayat (Jurnal Keislaman, 2022)
The Abbasid dynasty was the most successful Islamic dynasty in advancing Islamic civilization, among the aspects of progress made by this dynasty were the government system, the development of science and the development of Sufism at that time. The purpose of this study was to find out more specifically about the development of science, the system of government adopted and the development of Sufism in the Abbasid dynasty. Furthermore, the author uses a qualitative approach method with the type of library research by processing reading results, notes related to research sourced from journals, books and scientific articles and then processing them into library findings. To find out and analyze these findings, the authors apply the interactions used by Milles and Huberman, namely by selecting the information or data source, presenting the findings, and providing conclusions from the findings. From the analysis it is known that the development of science during the Abbasid dynasty developed very rapidly giving birth to religious and general science disciplines, forming scientific supporting facilities. In this dynasty the system of government adopted was a monarchical system, a caliph had a strong and solid authority in carrying out his duties and policies, and political policies had to be in line with religion. In carrying out the social life of the people in this dynasty, it was inseparable from the teachings of Sufism. Keywords: The development of science, the system of government, the science of Sufism. Abstrak Dinasti Abbasiyah adalah dinasti yang paling sukses dalam hal memajukan peradaban islam, diantara aspek kemajuan yang ditorehkan oleh dinasti ini adalah sistem pemerintahan, perkembangan ilmu pengetahuan dan perkembangan ilmu tasawuf pada masa itu. Tujuan penelitian ini untuk mengetahui lebih spesifik tentang perkembangan ilmu pengetahuan, sistem pemerintahan yang dianut dan perkembangan ilmu tasawuf yang ada pada dinasti Abbasiyah. Selanjutnya, penulis menggunakan Metode pendekatan kualitatif dengan jenis penelitian Kepustakaan dengan mengolah hasil bacaan, catatan terkait penelitian yang bersumber dari jurnal, buku-buku dan artikel ilmiah kemudian diolah menjadi hasil temuan pustaka. Untuk mengetahui dan menganalisis temuan tersebut, penulis menerapkan interaksi yang digunakan Milles dan Huberman yaitu dengan alur memilih informasi atau sumber data, menyajikan temuan, dan memberikan kesimpulan dari hasil temuan tersebut. Dari hasil analisis keilmuan pada dinasti abbasiyah berkembang sangat pesat serta melahirkan disiplin ilmu agama dan ilmu ilmu umum, membentuk fasilitas penunjang keilmuan. Pada dinasti ini sistem pemerintahan yang dianut adalah sistem monarki, seorang kholifah memiliki otoritas kuat dan kokoh dalam menjalankan tugas dan kebijakan, serta kebijakan politik harus sejalan dengan agama. Dalam menjalankan kehidupan sosial masyarakat pada dinasti ini tidak terlepas dari ajaran ilmu tasawuf. Kata kuci: Perkembangan ilmu pengetahuan, sistem pemerintahan, ilmu tasawuf.